2020
DOI: 10.1155/2020/8897029
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate and Spatiotemporal Analysis of Water Quality in Code River, Indonesia

Abstract: The efficacy of a water quality management strategy highly depends on the analysis of water quality data, which must be intensively analyzed from both spatial and temporal perspectives. This study aims to analyze spatial and temporal trends in water quality in Code River in Indonesia and correlate these with land use and land cover changes over a particular period. Water quality data consisting of 15 parameters and Landsat image data taken from 2011 to 2017 were collected and analyzed. We found that the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…Water quality parameters of the Code River were analyzed in previous studies, and it was found that both rural and city areas contribute to the bacterial load of the river. , One of the previous analyses revealed differences between the rural and city areas: A rural area roughly corresponding to Spring Water and Rural + Cattle Farm sites had lower concentrations of total dissolved solids, NO 2 – , NO 3 – , Zn, Cu, Pb, and lower biological and chemical oxygen demand than downstream sampling sites, which correspond to the city sampling area of this study. Detergent concentration and the abundance of fecal coliforms were higher in the city area (covering Hospital and City sites) than upstream (Spring Water and Rural + Cattle Farm sites) or downstream of the city (City Downstream).…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…Water quality parameters of the Code River were analyzed in previous studies, and it was found that both rural and city areas contribute to the bacterial load of the river. , One of the previous analyses revealed differences between the rural and city areas: A rural area roughly corresponding to Spring Water and Rural + Cattle Farm sites had lower concentrations of total dissolved solids, NO 2 – , NO 3 – , Zn, Cu, Pb, and lower biological and chemical oxygen demand than downstream sampling sites, which correspond to the city sampling area of this study. Detergent concentration and the abundance of fecal coliforms were higher in the city area (covering Hospital and City sites) than upstream (Spring Water and Rural + Cattle Farm sites) or downstream of the city (City Downstream).…”
Section: Resultsmentioning
confidence: 52%
“…Detergent concentration and the abundance of fecal coliforms were higher in the city area (covering Hospital and City sites) than upstream (Spring Water and Rural + Cattle Farm sites) or downstream of the city (City Downstream). The increased metal and detergent concentrations could partly explain the elevation of MGEs and related ARGs we observed in the city area, since MGEs commonly carry metal and quaternary ammonium compound resistance genes. ,, Concentrations of PO 4 3– and total suspended solids were higher in the rural area (Spring Water and Rural + Cattle Farm sites) than in the city area, possibly due to soil erosion . Although making statistical connections between previously analyzed water quality parameters , and the data of this study was not possible due to different numbers of samples and sampling times, the river quality parameters revealed that different sources contributed to the river contaminant load through different mechanisms.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations